2014
DOI: 10.1002/bdra.23269
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung's disease prevalence in Europe: A register based study

Abstract: This large population-based study found evidence of a small increasing trend in Hirschsprung's disease and differences in prevalence by geographic location. There was also no evidence of an association with maternal age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 13 publications
5
39
0
1
Order By: Relevance
“…This result is similar to what Ryan et al described, namely, that being firstborn decreased the risk for having HSCR. 23 Goldberg showed an association between maternal age and the risk for HSCR in the offspring, which could not be confirmed by Best et al or Russel et al 2,24,25 No correlation could be found between the risk of having a child with HSCR and maternal diseases. Our group previously reported a family with autosomal dominantly inherited HSCR associated with multiple sclerosis.…”
Section: Figurementioning
confidence: 88%
See 1 more Smart Citation
“…This result is similar to what Ryan et al described, namely, that being firstborn decreased the risk for having HSCR. 23 Goldberg showed an association between maternal age and the risk for HSCR in the offspring, which could not be confirmed by Best et al or Russel et al 2,24,25 No correlation could be found between the risk of having a child with HSCR and maternal diseases. Our group previously reported a family with autosomal dominantly inherited HSCR associated with multiple sclerosis.…”
Section: Figurementioning
confidence: 88%
“…1 Best et al recently reported a slightly increasing prevalence of HSCR in Europe. 2 HSCR is known to be a multifactorial disease caused by both genetic and environmental factors. Mutations in >10 genes have been associated with HSCR, particularly the RET gene, in which 15% to 20% of patients with isolated HSCR have mutations.…”
mentioning
confidence: 99%
“…The total prevalence of HSCR in Europe between years 1980-2009 was 1.09 per 10,000 births (26). In HSCR is a gender disparity among the patients, with the male to female ratio as high as 5 : 1.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies reported on a small but significant increase over the last three decades, HD remains a relatively rare congenital malformation with current prevalence rates of 1.09-1.63 per 10,000 live births [1,2]. The diagnosis of HD can be difficult as it relies on histological confirmation of complete absence of enteric ganglion cells in the myenteric and submucosal plexus of the distal rectum, which extends proximally for varying distance.…”
Section: Introductionmentioning
confidence: 99%